2018
DOI: 10.2174/1874285801812010243
|View full text |Cite
|
Sign up to set email alerts
|

Nontypable Haemophilus influenzae Septicemia and Urinary Tract Infection Associated with Renal Stone Disease

Abstract: Introduction: Haemophilus influenzae commonly causes upper respiratory tract infections and has only rarely been reported etiology of urinary tract infections. Since the introduction of the Haemophilus influenzae b (Hib) vaccine, non-typable haemophilus species now cause the majority of invasive disease in Europe.Case Report:We report a case of an adult man with non-typable Haemophilus influenzae septicemia, urinary tract infection and bilateral renal stone disease. The patient presented with right sided flank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Invasive disease had a higher incidence in individuals over 65 years of age, in line with the underlying conditions that are more common in older adults such as COPD, heart disease and diabetes [8,29,30]. By contrast, young adults presented more cases of invasive disease due unusual origins, such as peritonitis, liver abscess, endometritis, facial cellulitis or urinary tract infection, which, although less common, typically affect immunocompetent young adults [31][32][33]. The overall 30 day mortality was 18.0 %, within the range of 10-20 % found in other studies [34][35][36].…”
Section: Discussionmentioning
confidence: 95%
“…Invasive disease had a higher incidence in individuals over 65 years of age, in line with the underlying conditions that are more common in older adults such as COPD, heart disease and diabetes [8,29,30]. By contrast, young adults presented more cases of invasive disease due unusual origins, such as peritonitis, liver abscess, endometritis, facial cellulitis or urinary tract infection, which, although less common, typically affect immunocompetent young adults [31][32][33]. The overall 30 day mortality was 18.0 %, within the range of 10-20 % found in other studies [34][35][36].…”
Section: Discussionmentioning
confidence: 95%
“…Haemophilus spp. is reported as a rare urinary tract pathogen but needs to be investigated in patients with urinary tract abnormalities such as urolithiasis [ 36 ]. A previous study demonstrated that Faecalibacterium was more abundant in patients with diabetes mellitus (DM) and hyperlipidemia, compared to patients with only DM, as seen in the study by Fengping Liu et al They also demonstrated that Faecalibacterium is associated with incidence of UUI.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, pneumonia is the most frequent presentation, with invasive NTHi disease and NTHi pneumonia incidence increasing with age, particularly in older adults with underlying respiratory tract comorbidities, such as COPD and emphysema (204,208). Other clinical presentations, such as epiglottitis (once a characteristic of invasive Hib disease) and skeletal and soft tissue infections, are uncommon, but cholecystitis (209) and urolithiasis (210) appear to be a particular feature of invasive NTHi infection in adults. The morbidity rate of invasive NTHi infections is high in older adults.…”
Section: Nthi Infections In Older Adultsmentioning
confidence: 99%